2007
DOI: 10.1186/1471-2148-7-99
|View full text |Cite
|
Sign up to set email alerts
|

A genetically explicit model of speciation by sensory drive within a continuous population in aquatic environments

Abstract: Background: The sensory drive hypothesis predicts that divergent sensory adaptation in different habitats may lead to premating isolation upon secondary contact of populations. Speciation by sensory drive has traditionally been treated as a special case of speciation as a byproduct of adaptation to divergent environments in geographically isolated populations. However, if habitats are heterogeneous, local adaptation in the sensory systems may cause the emergence of reproductively isolated species from a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 77 publications
(130 reference statements)
0
40
0
Order By: Relevance
“…One aspect of our study system that is not captured by classical models of clinal speciation is that the observed depth cline appears only to be limited to the spawning season. A key aspect of many clinal speciation models is that dispersal is limited along the environmental gradient, decreasing gene flow and increasing the fitness consequences of localized selection regimes (Doebeli & Dieckmann, 2003; Heinz, Mazzucco, & Dieckmann, 2009; Kawata et al., 2007). Yet, whitefish outside the spawning season disperse over much greater distances than the geographic extent of the spawning gradient and indeed this study found co‐occurrence of multiple species within certain depths during the spawning season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect of our study system that is not captured by classical models of clinal speciation is that the observed depth cline appears only to be limited to the spawning season. A key aspect of many clinal speciation models is that dispersal is limited along the environmental gradient, decreasing gene flow and increasing the fitness consequences of localized selection regimes (Doebeli & Dieckmann, 2003; Heinz, Mazzucco, & Dieckmann, 2009; Kawata et al., 2007). Yet, whitefish outside the spawning season disperse over much greater distances than the geographic extent of the spawning gradient and indeed this study found co‐occurrence of multiple species within certain depths during the spawning season.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical work suggests that speciation is more likely to occur when populations are spatially structured along environmental gradients rather than in complete geographic overlap, as divergent selection regimes encountered at different locations along the gradient act on both phenotypic traits related to ecology and those related to reproductive isolation to reduce homogenizing gene flow (Doebeli & Dieckmann, 2003; Endler, 1977; Gavrilets, 2004; Kawata, Shoji, Kawamura, & Seehausen, 2007; Lande, 1982; Payne, Mazzucco, & Dieckmann, 2011). Given the ubiquity of environmental gradients in nature, clinal speciation along such gradients might be an important generator of new species (Doebeli & Dieckmann, 2003; Gavrilets, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In sexual systems, processes such as assortative mating (Pryke, 2010) and alternative reproductive tactics (Sinervo & Lively, 1996) are known drivers of colour polymorphism. Theoretical and empirical evidence has also demonstrated the potential for sensory drive to maintain variation, including polymorphism, in sexual signalling systems (Chunco, McKinnon, & Servedio, 2007;Kawata, Shoji, Kawamura, & Seehausen, 2007;Kolm et al, 2012;McNaught & Owens, 2002;Seehausen et al, 2008). There is of course no reason to expect the influence of sensory drive to apply exclusively or disproportionately to sexual signalling systems.…”
Section: Colour Lure Systems As a Testing Ground For Theorymentioning
confidence: 91%
“…The differentiation of visual perception and nuptial coloration implies the divergence of color signals. The process of adaptive divergence of color signals caused by ecological selection is known as "sensory drive" (Endler, 1992;Boughman, 2002;Kawata et al, 2007). The divergence of color signals observed in N. greenwoodi is well matched with the process of sensory drive, and populations of N. greenwoodi may be at the incipient stage of speciation by sensory drive (Fig.…”
Section: Divergences Of Lws Alleles and Nuptial Colorations Lead To Smentioning
confidence: 99%
“…1) (e.g., Seehausen, 1996), and sexual selection via female choice of male coloration has played an important role in the evolution of Lake Victoria cichlids (Seehausen et al, 1997aMaan et al, 2006). Model simulations propounded the theory that local adaptations of the visual system to different light environments caused divergence of color via signal matching to the adapted perception of mates (Kawata et al, 2007). Recently, analyses of male color and vision in cichlids revealed that color signal divergence leads to speciation in nature, supporting this model .…”
Section: Introductionmentioning
confidence: 99%